RELIGIOUS AXIOLOGY IN WARTIME THROUGH THE PRISM OF ORTHODOX ANTHROPOLOGY AND THE EUROPEAN VALUE SPACE - Tselkovskyi, Hennadii; Skladan, Andrii; Aparshin, Ivan (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2026)
Introduction. The article examines religious axiology in the context of the Russian-Ukrainian war through the prism of Orthodox anthropology and the European value space. Particular attention is paid to human dignity, freedom, solidarity, responsibility, and the role of religious media in wartime. The aim and tasks. The aim of the study is to analyze religious axiology in the context of the Russian-Ukrainian war through Orthodox anthropology and European values. The tasks are to identify the core values of Orthodox anthropology, clarify the normative foundations of the European value order, determine the points of convergence and tension between them, and analyze the role of religious media and digital communication in the circulation of values. Research methods. The research combines axiological, comparative, hermeneutic, and discourse-analytical approaches. Theological, philosophical, legal, and media texts are analyzed in correlation with contemporary studies on war, religion, and digital communication. Research results. The study demonstrates that Orthodox anthropology interprets the human being as the image and likeness of God and therefore as a bearer of dignity, freedom, and responsibility. War appears not only as a political conflict but also as an anthropological crisis affecting the foundations of human coexistence. At the same time, the European value space reveals substantial convergence with the Orthodox personalist understanding of the person, although these values are expressed primarily in legal and political language. The analysis also shows that religious values are increasingly mediated through religious media and digital communication. Discussion. The main tension between Orthodox and European axiologies concerns not the values themselves, but the modes of their justification and social legitimation. In the Ukrainian wartime context, this tension is intensified by competing religious and political narratives. Conclusions. Religious axiology in wartime acquires theological, social, and communicative significance. Religious values become socially constructive when they support human dignity, freedom, solidarity, and responsibility.